2001
DOI: 10.1161/01.hyp.37.2.599
|View full text |Cite
|
Sign up to set email alerts
|

Differential Inhibition of Functional Dilation of Small Arterioles by Indomethacin and Glibenclamide

Abstract: Abstract-Indomethacin or glibenclamide treatments attenuate functional dilation of larger-diameter "feed" arterioles paired with venules in hamster cremaster muscle. We tested the hypothesis that release of cyclooxygenase products from venules is important for functional dilation of third-and fourth-order arterioles. We also tested whether ATP-sensitive potassium channels are important during functional dilation of smaller arterioles. The microcirculation of hamster cremaster muscle was visualized with in vivo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
37
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 16 publications
8
37
0
Order By: Relevance
“…Similar results were also found in patients with type 2 diabetes (14). Because previous studies have supported a critical role of prostaglandin(s) in mediating functional vasodilation (10,19,20,24,30), it is possible that the impaired functional vasodilation in metabolic syndrome may be due to altered AA metabolism. Indeed, previous studies have shown that urinary thromboxane B 2 excretion is enhanced in 12-wk-old OZRs associated with an increased cyclooxygenase-2 expression in kidney (3,15).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Similar results were also found in patients with type 2 diabetes (14). Because previous studies have supported a critical role of prostaglandin(s) in mediating functional vasodilation (10,19,20,24,30), it is possible that the impaired functional vasodilation in metabolic syndrome may be due to altered AA metabolism. Indeed, previous studies have shown that urinary thromboxane B 2 excretion is enhanced in 12-wk-old OZRs associated with an increased cyclooxygenase-2 expression in kidney (3,15).…”
Section: Discussionsupporting
confidence: 80%
“…Indeed, the role of NO in mediating functional vasodilation in humans and animals is still unclear. Our previous study showed that, in the cremaster muscle, inhibition of cyclooxygenase with indomethacin significantly attenuates functional dilation (19,24), suggesting that prostaglandins play a central role in functional hyperemia (10). Indeed, endothelial-derived prostacyclin (PGI 2 ) has been proposed as playing an important role in regulating local blood flow during exercise through activation of PGI 2 receptors prostacyclin (IP) on vascular smooth muscle cells (20,30).…”
mentioning
confidence: 99%
“…The authors speculate that these vessels are alternative drainage routes for the blood, which could prevent a rapid washout of the end products of myocardial metabolism, allowing for prolonged arterial vasodilation. In the hamster cremaster muscle, pairing usually persists down to the arterioles, which are two or three generations upstream from the capillaries (20,38). Depending on the nomenclature used to classify the arterioles of the microcirculation, these smaller paired vessels give rise to the transverse arterioles (38) or unpaired third-or fourth-order arterioles (20).…”
Section: Anatomical Evidence For Venular-arteriolar Communicationmentioning
confidence: 99%
“…In the hamster cremaster muscle, pairing usually persists down to the arterioles, which are two or three generations upstream from the capillaries (20,38). Depending on the nomenclature used to classify the arterioles of the microcirculation, these smaller paired vessels give rise to the transverse arterioles (38) or unpaired third-or fourth-order arterioles (20). As noted in the previous paragraph, arterioles upstream from the transverse arterioles provide the most resistance to blood flow within a vascular bed and it is these vessels that are tightly paired with venules.…”
Section: Anatomical Evidence For Venular-arteriolar Communicationmentioning
confidence: 99%
“…An alternative explanation is that another mediator diffuses from venule to arteriole in the NO-dependent dilatory mechanism. Cyclooxygenase metabolites play a major role in venule-mediated arteriolar dilation in functional hyperemia, but possibly not in resting conditions (7). Adenosine is a potent vasodilator in many vascular beds, and adenosine release is increased during hypoxia, ischemia, or metabolic stress, when O 2 delivery is inadequate to meet the tissue demand (18,32).…”
mentioning
confidence: 99%